The biological preparations for plant protection in organic farming - Volosciuc, L. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
Consider new directions for biotechnology, creating conditions for the development of chemical and biological plant protection, their rational levels and proportions. The article aimed to present the problems of plant protection in ecological agriculture, using the possibilities of modern biotechnology. Application traditional technologies demonstrate indispensable contradiction between the plant protection requirements condition and the need to preserve environment. The systemic approach of relations between crop and pests opens new possibilities in researching biocenotic relationships within ecosystems and halting spending growth trends directed to plant protection. Parting from the aggravation of ecological situation and taking into account the achievements in the field of biological plant protection, in the Republic of Moldova consistent measures have been undertaken in the direction of ecological agriculture promotion. For solving of plant protection problems were developed biotechnological processes of production and application of an impressive range of biological means, which is used for conventional and organic agriculture. The main legislative documents (Low No 115 from 2005 concerning the ecological agriculture, Government decision No 149 from 2006 concerning its implementation, a series of regulations) have been adopted. The results relative to production organization, processing and marketing of ecological products are being registered, but a series of the technological problems remains which are waiting their solution.